Sustainable Energy Management Strategies in Reducing the Impact of Fossil Energy on Climate Change and Green Energy Implementation in the Business Sector - Rianti Salima; Aep Saefullah; Arief Sahreza; Fuad Siregar (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to examine the management of environmental risks arising from the use of fossil energy and strategies for transitioning to green energy in the business sector. The main focus of the research is to analyze the managerial role in facing environmental regulatory challenges, as well as how leaders and managers can develop a culture of sustainability within the organization. This research uses a qualitative approach with in-depth interview techniques and document analysis on large companies in the industrial and manufacturing sectors that have adopted or are transitioning to green energy, in the period June-September 2024. The results show that companies that successfully reduce environmental risks have a clear and strong energy transition strategy, including investments in green technology and managerial training related to sustainability. The biggest challenges faced are government policy uncertainty and the high costs involved in green energy implementation. In addition, this study also highlights the important role of visionary leaders and competent managers in driving organizational culture change towards sustainability. The implication of this research is the importance of a proactive, innovative management approach and compliance with environmental regulations in the face of green energy transition.